2022
DOI: 10.1101/2022.07.12.22277517
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Application of Atraumatic Care Philosophy to Children in Hospitals a Literature Review

Abstract: Background: Hospitalization for children has an impact on physical and psychological problems for children and parents. Many interventions can be done to reduce stressors for children or parents in nursing using the philosophy of atraumatic care, but there are not many articles that provide specific identification in the realm of the philosophy of atraumatic care. This study aims to determine the Evidence-Based Practice Nursing (EBPN) atraumatic care carried out by nurses in hospitals. Method: This research us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…They can also be involved in therapy and collaborate with experts to give their children the most ideal consideration. Parental participation in atraumatic care while the child is hospitalized, based on the results of the review of the articles above, includes emotional support, distraction techniques, comfort measures, communication and education, advocacy, collaboration with the healthcare team, participating in care routines, and providing post-procedure comfort (Handayani & Daulima, 2020;Ilmiasih & Ningsih, 2022;Jerofke-Owen et al, 2022;van Oort et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They can also be involved in therapy and collaborate with experts to give their children the most ideal consideration. Parental participation in atraumatic care while the child is hospitalized, based on the results of the review of the articles above, includes emotional support, distraction techniques, comfort measures, communication and education, advocacy, collaboration with the healthcare team, participating in care routines, and providing post-procedure comfort (Handayani & Daulima, 2020;Ilmiasih & Ningsih, 2022;Jerofke-Owen et al, 2022;van Oort et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…During a child's hospital stay, parental involvement and emotional support are crucial components of pediatric care. Research has demonstrated that the presence of parents and their involvement in atraumatic care improves the well-being of hospitalized children (Handayani & Daulima, 2020;Ilmiasih & Ningsih, 2022). Additionally, while a baby is in the hospital, medical staff can support parents in their roles as primary caregivers and decision-makers and address the psychological effects of the hospital stay on the family (Gramszlo et al, 2020).…”
Section: Discussionmentioning
confidence: 99%